Observational outcome in surgery for Chiari malformation patients - Parmar, Harisinh; Shah, Jaimin K.; Gaud, Jayant; Solanki, Shailendra J.; Mavani, Jatin; Baru, Dhruv (International Surgery Journal, 2020)
Chiari malformation is the commonest anomaly of the craniovertebral junction involving both the skeletal as well as the neural structures. It is congenital anomaly of the hindbrain characterised by downward elongation of the brain stem and cerebellum into the cervical portion of spinal cord. Most common presenting symptoms was pain in the nape of neck with sub-occipital headache and weakness. If not intervened early in these cases they may progress to quadriparesis and respiratory failure. This study includes authors experience of 30 surgical corrections of Chiari malformation performed at civil hospital Ahmedabad from 2017 to 2019. The age and sex of the patient, the presence of syrinx, the type of surgical procedure and the clinical outcome were determined post-operatively and on follow up. Cerebro spinal fluid leak and collection were observed in patient who undergone duroplasty only with no leakage in patient undergone syringo-subarachnoid shunt. Overall, tingling/numbness had best improvement showed improvement in 13 out of 16 patients. Power showed improvement in 20 out of 27 patients and pain showed improvement in 18 patients. Wasting, clawing and cerebellar signs and bony deformity showed no improvement in any of the above procedures. Authors can conclude for Chiari malformation decompression with or without duroplasty with additional procedure with post-operative physiotherapy and analgesia is the suitable treatment.